2017
DOI: 10.1111/asj.12880
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis to unravel the effect of heat stress on gene expression and milk synthesis in bovine mammary epithelial cells

Abstract: Heat stress can play a negative effect on milk yield and composition of dairy cattle, leading to immeasurable economic loss. The basic components of the mammary gland are the alveoli; these alveolar mammary epithelial cells reflect the milk producing ability of dairy cows. In this study, we exposed bovine mammary epithelial cells to heat stress and compared them to a control group using isobaric tags for relative and absolute quantitation combined with liquid chromatography coupled with tandem mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
2
5
1
1
Order By: Relevance
“…We compared the CSN1S1 , CSN2 , and CSN3 genes expression, which are the most highly expressed casein genes in milk protein [ 49 ], between the HS and CON groups and found that their expressions were significantly decreased in the HS group. These findings corroborate an earlier research report on the mammary gland tissue of heat-stressed lactating dairy cows [ 50 ] and another study on heat-stressed BMECs [ 51 ]. Therefore, heat stress could directly inhibit the synthesis of casein proteins, and the decrease in the DMI may be partly responsible for the decrease in the synthesis of milk protein in lactating cows under heat stress.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We compared the CSN1S1 , CSN2 , and CSN3 genes expression, which are the most highly expressed casein genes in milk protein [ 49 ], between the HS and CON groups and found that their expressions were significantly decreased in the HS group. These findings corroborate an earlier research report on the mammary gland tissue of heat-stressed lactating dairy cows [ 50 ] and another study on heat-stressed BMECs [ 51 ]. Therefore, heat stress could directly inhibit the synthesis of casein proteins, and the decrease in the DMI may be partly responsible for the decrease in the synthesis of milk protein in lactating cows under heat stress.…”
Section: Discussionsupporting
confidence: 93%
“…between the HS and CON groups and found that their expressions were significantly decreased in the HS group. These findings corroborate an earlier research report on the mammary gland tissue of heatstressed lactating dairy cows [50] and another study on heat-stressed BMECs [51]. Therefore, heat stress could directly inhibit the synthesis of casein proteins, and the decrease in the DMI may be partly…”
Section: A C C E T E Dsupporting
confidence: 91%
“…It is well known that stress exposure during lactation affects milk constituents and milk yield. Some studies have showed that stress decreases the yield of milk and concentrations of milk proteins such as casein in bovine and mice [ 27 , 35 , 36 ]. Additionally, the level of secretary immunoglobulin IgA in breast milk is negatively corelated with a negative Profile of Mood State, which is an index of psychological states such as tension-anxiety, depression-dejection, anger-hostility, fatigue, and confusion [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bionaz and Loor, 2008;Qi et al, 2014 • High expression of FASN means that it plays an essential role for fatty acid synthesis, however it has significantly lower expression in heat-treated bovine mammary epithelial cell which suggests that fatty acid synthesis might affected by heat stress. Zhu et al, 2014;Li et al, 2017 nitrogen levels compared to animals under thermally neutral controls (Bernabucci et al, 2010). BUN can either originate from the inefficient incorporation of rumen ammonia into microbial proteins or from hepatic deamination of amino acids mobilized in skeletal muscles (Bernabucci et al, 2010).…”
Section: Matés Et Al 1999mentioning
confidence: 99%